2023
DOI: 10.1007/s11032-022-01354-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and marker-trait relationships of functional markers for glutamine synthetase GS1 and GS2 homoeogenes in bread wheat

Abstract: GS1 and GS2 genes encode, respectively, the main cytosolic and the plastidic isoforms of glutamine synthetase (GS). In the present study, the wheat GS1 and GS2 homoeogenes located in the A, B and D genome chromosomes have been sequenced in a group of 15 bread wheat varieties including landraces, old commercial varieties and modern cultivars. Phenotypic characterization by multi-environment field trials detected significant effects of specific GS homoeogenes on three of the seven agronomic and grain quality tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Functional markers (FMs), a type of molecular marker developed based on the variation of cloned functional genes, are completely associated with the target trait and, therefore, have great superiority. Functional genetic markers can reduce the genetic burden of progeny selection, greatly improving selection accuracy (Pascual et al, 2023). Currently, multiple melon genomes have been assembled and annotated, and some genes controlling important agronomic traits of melons have been cloned (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Functional markers (FMs), a type of molecular marker developed based on the variation of cloned functional genes, are completely associated with the target trait and, therefore, have great superiority. Functional genetic markers can reduce the genetic burden of progeny selection, greatly improving selection accuracy (Pascual et al, 2023). Currently, multiple melon genomes have been assembled and annotated, and some genes controlling important agronomic traits of melons have been cloned (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…GS is a key enzyme involved in NH4 + , which can convert inorganic ammonium salts in plant into organic N [12]. Studies have shown that the role of GS activity in response to fertilization has been widely investigated, and its relationship with stresses such as drought and high temperature has also been explored [13]. In most plants, GS exists in two forms, including cytoplasmic GS1 and chloroplasts GS2 [14].…”
Section: Introductionmentioning
confidence: 99%